Effect of Narrative Writing Intervention on Work Stress Among Employees with Consideration of Self-Disclosure - Rizqa Fithra Ramadhani; Rita Markus Idulfilastri; Ninawati Ninawati (Green Publisher Indonesia, 2025)
Corporate acquisitions often trigger structural changes that heighten employee stress. Such changes can create anxiety and uncertainty regarding job positions and levels of control, particularly among employees who worked in the company prior to the acquisition. This study examines the Effect of Narrative Writing Intervention on Work Stress Among Employees with Consideration of Self-Disclosure. Using a quantitative experimental method, participants were divided into two groups: an experimental group that wrote about experiences and emotions related to work stress, and a control group that wrote about daily activities without expressing emotions or personal feelings. The instruments used were the 10-item Perceived Stress Scale (Cohen & Williamson, 1988) and the Modified 10-item Self-Disclosure Index (Miller et al., 2011). Findings indicate that self-disclosure enhances the effectiveness of narrative writing, as individuals with higher levels of self-disclosure were better able to process emotions and benefited more from the writing activity. A total of eight participants were evenly assigned to each group, based on their status before and after the company acquisition. Results showed that narrative writing functioned as a dynamic emotional process. Stress levels initially increased during the early intervention weeks but subsequently decreased significantly. Self-disclosure played a crucial role in this process, with participants reporting higher self-disclosure experiencing greater reductions in stress.